Functional Labour Market Areas for Chile - Rowe, Francisco; Casado-Díaz, José Manuel; Martínez-Bernabéu, Lucas (REGION, 2017)
Administrative areas are arbitrarily designed and do not necessarily reflect the geographical patterns of socio-economic and labour market activity. Labour market areas (LMAs) are required to analyse spatial labour market activity and provide a framework to guide spatially-explicit employment policy development. This resource describes a data source of a set of recently created labour market areas for Chile.